Molecular evidence of sequential evolution of DDT- and pyrethroid-resistant sodium channel in Aedes aegypti. - Mengli Chen; Yuzhe Du; Shaoying Wu; Yoshiko Nomura; Guonian Zhu; Boris S Zhorov; Ke Dong (Public Library of Science (PLoS), 2019)
Background Multiple mutations in the voltage-gated sodium channel have been associated with knockdown resistance (kdr) to DDT and pyrethroid insecticides in a major human disease vector Aedes aegypti. One mutation, V1016G, confers sodium channel resistance to pyrethroids, but a different substitution in the same position V1016I alone had no effect. In pyrethroid-resistant Ae. aegypti populations, V1016I is often linked to another mutation, F1534C, which confers sodium channel resistance only to Type I pyrethroids including permethrin (PMT), but not to Type II pyrethroids including deltamethrin (DMT). Mosquitoes carrying both V1016G and F1534C exhibited a greater level of pyrethroid resistance than those carrying F1534C alone. More recently, a new mutation T1520I co-existing with F1534C was detected in India. However, whether V1016I or T1520I enhances pyrethroid resistance of sodium channels carrying F1534C remains unknown. Methodology/principal findings V1016I, V1016G, T1520I and F1534C substitutions were introduced alone and in various combinations into AaNav1-1, a sodium channel from Aedes aegypti. The mutant channels were then expressed in Xenopus oocytes and examined for channel properties and sensitivity to pyrethroids using the two-electrode voltage clamping technique. The results showed that V1016I or T1520I alone did not alter the AaNav1-1 sensitivity to PMT or DMT. However, the double mutant T1520I+F1534C was more resistant to PMT than F1534C, but remained sensitive to DMT. In contrast, the double mutant V1016I+F1534C was resistant to DMT and more resistant to PMT than F1534C. Furthermore, V1016I/G and F1534C channels, but not T1520I, were resistant to dichlorodiphenyltrichloroethane (DDT). Cryo-EM structures of sodium channels suggest that T1520I allosterically deforms geometry of the pyrethroid receptor site PyR1 in AaNav1-1. The small deformation does not affect binding of DDT, PMT or DMT, but in combination with F1534C it increases the channel resistance to PMT and DDT. Conclusions/significance Our data corroborated the previously proposed sequential selection of kdr mutations in Ae. aegypti. We proposed that mutation F1534C first emerged in response to DDT/pyrethroids providing a platform for subsequent selection of mutations V1016I and T1520I that confer greater and broader spectrum of pyrethroid resistance.